Quality Assurance of a "Booster Program" for Gender Equity in the Academia: From Vision to Practice - Bitton, Yifat; Zamir , Sara (Journal of Ecohumanism, 2024)
Even as the 21st century unfolds, it is well recognized that women in the academic world struggle more to secure research funding and are still largely underrepresented at the level of full professorship, the highest post possible within universities and colleges. To rectify this gender-based inequality, a mid-sized academic college initiated an original program named "Booster" aiming for it to provide the optimal framework for creating a nurturing space for the promotion of prominent female faculty members, mainly to the high rank of "professor." The aim of this research was to find whether the booster plan has fulfilled its rectifying objectives according to the quality assurance model of the Plan - Do - Check - Action (PDCA) cycle. As a research method, an evaluation study was selected to examine the operation of the program, mainly from the perspective of the participants. The evaluation of the program was combined with both quantitative and qualitative assessments. The main finding indicated that the participants in the program had reported a high-level satisfaction. It was also found that the vast majority of the participants mentioned their understanding of promotion procedures as the most important tool they acquired in the program. The main importance of this study is in adding knowledge about ways to identify the "blind spots" and weaknesses of academia that shape the unjust "leaky pipeline" structure in gender contexts, from the stage in which women enter academia, through their tenure- ship track as faculty, to the processes of promotion up the ranks.